A novel combined vaccine against classical swine fever and porcine epidemic diarrhea viruses elicits a significant Th2-favored humoral response in mice. Issue 33 (30th July 2021) - Ding, Yanbin; Luo, Lingzhi; Luo, Ye; Zhao, Dun; Mi, Shijiang; Yu, Xiaohang; Zheng, Jin; Tu, Changchun; Yu, Xinglong
Abstract: Many Chinese breeding pigs are repeatedly vaccinated against classical swine fever virus (CSFV) and porcine epidemic diarrhea virus (PEDV), which cause fatal, highly contagious diseases. To reduce their high frequency vaccination-induced immune stress, we constructed a combined vaccine based on the E2 protein of CSFV and the S1 spike protein subunit of PEDV (named E2-S1). In mice, the E2-S1 vaccine elicited higher neutralizing antibody titers and IgG1/IgG2a ratios against CSFV and PEDV than those induced by individual E2 or S1 vaccines. Moreover, it elicited high IL-4 expression, but no IFN-γ expression. The results suggest that good compatibility exists between E2 and S1 antigens, and the E2-S1 vaccine can elicit a strong Th2-type cell-mediated humoral immune response. The E2-S1 recombinant fusion protein provides a novel vaccine candidate against both CSFV and PEDV, laying the foundation for future combination vaccines against swine diseases.